The Influence of Entrepreneurship and Digital Marketing on Sustainable Economic Development - Warsiman, Warsiman; Ekowati, Dhiana; Kholisoh, Luluk; Supardi, Supardi; Susilawati, Rini (Integrated Journal of Business and Economics (IJBE), 2024)
Sustainable economic development is a process that balances the recovery of economic growth by considering the environmental and social impacts of society in improving the economy. It is one of the practical tools for strategic adaptation to achieve economic and environmental sustainability. This encourages entrepreneurs to create businesses that use skills and initiative to meet needs and bring new ideas. Understanding these opportunities has brought the resulting products to the attention of the market. To support this, a strategy that can be implemented is digital marketing. This is important for business continuity and reaching the community or even getting customers. This research aims to determine and analyze entrepreneurship and digital marketing towards sustainable economic development. Quantitative methods are used, especially questionnaires. The results of a sample of 30 respondents show that entrepreneurship has no effect on sustainable economic development, but is positive and not significant. Meanwhile, digital marketing has a positive and significant influence on sustainable economic development.